THE PEDAGOGICAL IMPARTIALITY REQUIREMENT IN QUEBEC’S ETHICS AND RELIGIOUS CULTURE CURRICULUM: IS IT CONSISTENT WITH TEACHER AUTONOMY AND CHARTER RIGHTS? - Maxwell, Bruce (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2019)
Quebec’s Ethics and Religious Culture program (ERC) requires teachers to adopt a professional stance of pedagogical impartiality. This article examines the complex regulatory framework surrounding the impartiality requirement from the perspectives of teachers’ legally recognized right to professional autonomy, their constitutional rights to religious freedom and freedom of expression, and the related issue of impartiality as a pedagogical device when teaching about controversial issues. The paper’s brief review of the jurisprudence does not support a decisive answer to the question of whether the legal basis of the impartiality ERC’s impartiality requirement is sound. However, it does reveal that the impartiality requirement is more legally fragile than it might appear at first glance.